2016
DOI: 10.4172/2332-0702.1000200
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Palatal Coverage on the Retention Force and Fatigue Resistance of Mini Dental Implant Maxillary Overdenture

Abstract: Purpose: evaluation and comparison of the influence of palatal coverage on the retention force and fatigue resistance of attachment system of mini dental implant (MDIs) overdenture. Materials and methods:heat-cured polymethylmethacrylate resin maxillary acrylic resin models were used for this study. Five 2.5 × 13 mm dummy mini-dental implants with O-ring attachment were placed parallel to each other. Ten palateless implant retained overdenture, and ten full coverage implant retained overdenture were constructe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…[ 6 ] Bar–clip constructions or nonsplinted concept attachments are used for retaining these overdentures. [ 7 ] Literature demonstrated the use of telescopic attachments as a retentive aid in implant-supported overdentures. The main effect of these attachments is transmission of occlusal forces along the long axis of abutment, and hence ensures the long life of prostheses.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] Bar–clip constructions or nonsplinted concept attachments are used for retaining these overdentures. [ 7 ] Literature demonstrated the use of telescopic attachments as a retentive aid in implant-supported overdentures. The main effect of these attachments is transmission of occlusal forces along the long axis of abutment, and hence ensures the long life of prostheses.…”
Section: Discussionmentioning
confidence: 99%
“…Although numerous studies have shown that the palate less four-implant retained maxillary overdenture is a simple and effective solution and leads to significant improvement of patient-based outcomes. (4)(5)(6)(7) The increased load concentration over the implants may cause loosening of the attachments mucosal ulceration and implant overload (10)(11)(12) .…”
Section: Discussionmentioning
confidence: 99%
“…(1)(2)(3) Numerous studies have shown that U-shaped palate-less maxillary implant-retained overdenture is an effective solution and leads to significant improvement of patient-based outcomes, increased quality of life, and provide easier access for oral hygiene. (4)(5)(6)(7) A systematic review on maxillary implant-retained overdentures showed that there are no specific guide lines for the number of implants necessary to support a maxillary implant-retained overdenture. Some authors have reported clinical success as determined by survival of prostheses and implants in treating patients with a palate-less maxillary implant-retained overdenture with a minimum of 4 supporting implants, while others recommended the use of palatal coverage when 4 or less implants are used.…”
Section: Introductionmentioning
confidence: 99%
“…Before retention evaluation, artificial saliva (Saliveze TM -Wyvern Medical LTD-UK) was applied to the models and the inner side of the overdentures framework to mimic the oral environment [26]. Retention was estimated by a digital force gauge (Nextech DFS500-Nextech Global-Thailand) used to record maximum dislodging forces [27], [28] (Fig.…”
Section: Retention Evaluation Processmentioning
confidence: 99%